Methods of critical thinking in classes of philological disciplines in higher education institutions: neuroscientific approach - Tamozhska, Iryna; Kosarieva, Halyna; Vasylenko, Oksana; Breslavets, Nadiia; Anikina, Inessa; Mordovtseva, Nataliia (Academia EduSoft і Lumen publishing, 2022)
The relevance of the research in the context of determining an importance of critical thinking lies in the excessive informatization of a modern society. The Internet is becoming a source of a large flow of an information, which is spread through the intensive use of an information and communication technologies in almost all areas of human life. The article highlights features of a digitalization in the modern world, as well as the main methods of critical thinking for an analysis and an evaluation of an information.The research work is based on theoretical and methodological approaches of researchers of critical thinking as a method, in particular in the field of philology. Theoretical and methodological approaches of the research became the basis for determining results of an effective implementation of critical thinking methods in philological classes in higher education institutions in the context of a neuroscientific approach. In order to study the effectiveness of the use of critical thinking in philological specialties some research, descriptive and scientific methods were used. The method of an analysis was also used in the context of distinguishing the concept of a method, critical thinking, specialties of philology and a neuroscientific approach. To determine the main results of the research, a generalization method was used. Results of the research became the basis for a need to think critically in the modern historical space, as digitalization of the society has led to a continuous flow of an information, which causes the infodemia as destabilizing factor in a public life. Also, future professionals in obtaining a qualification must clearly distinguish the true information from an inaccurate, which can be realized in the presence of a critical perception of an information flow.
Accession Number WOS: 000935025400028
Keywords: competent qualification; self-realization; self-affirmation; neuropedagogy; media resources; HUMANITIES and RELIGION